Ultrasonography in the diagnosis of pediatric distal forearm fracture: a systematic review - Ahmed Ayman S.; Abdelhady Ahmed E. (Journal of Ultrasonography)
Distal forearm fractures are one of the commonest injuries in children due to falling on an outstretched hand. Plain X-ray is the gold standard test for diagnosing fractures of long bones but it exposes patients to radiation with its associated health hazards. The use of ultrasonography has been proposed as a safer diagnostic test. This review aimed to summarize the evidence regarding the diagnostic accuracy of bedside ultrasonography for identifying distal forearm fractures in pediatric patients.